Indonesia’s South China Sea Policy under Joko Widodo: Building Credibility in Indo-Pacific Geostrategic Circuit - Irsadanar, Rafyoga Jehan Pratama (Jurnal Hubungan Internasional, 2023)
This research explains how states’ expanding security policy contributes to its credibility of threats in international relations. The context is represented by the case of Indonesia’s South China Sea policy expansion under Joko Widodo administration, which became more assertive. Most of the current literatures picture Indonesia’s South China Sea engagement in the setting of its relation with China and its effort to build regional stability. This paper aims to locate the case of Indonesia’s South China Sea policy into a broader context of Indo-Pacific geostrategic landscape. To achieve this objective, this research utilized credibility concept in international relations as analytical framework. This research argues that Indonesia’s bolder and more institutionalized security policy in navigating South China Sea stand-offs aims to build its credibility of threat in Indo-Pacific circuit. With more credibility of threat, it expects to escalate Indonesia’s strategic positioning as it has more credibility to deter China’s intrusion. By that, Indonesia is seen to be more reliable to maintain the maritime stability and lead more strategic partners be more committed to cooperate with Indonesia, as the linchpin connecting Indian Ocean and Pacific Ocean.